2017
DOI: 10.7160/aol.2017.090207
|View full text |Cite
|
Sign up to set email alerts
|

A Low Cost Irrigation System with Raspberry Pi – Own Design and Statistical Evaluation of Efficiency

Abstract: Nowadays is automation a permanent part of ordinary households and subject to constant evolution. Standard of home automation is a smart (intelligent) home that meets the requirements of the owner and gives him considerable comfort. To the offer of solutions, the intelligent home includes, are control of lighting and temperature, camera system or irrigation system. Technologies of an irrigation system are being developed with an emphasis on smart management of water, advanced features and remote control of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The use of ontologies in IoT applications allows better results in terms of interoperability between devices. Koprda, Š, et al [18] indicates new trends in irrigation systems and presents the design, implementation and evaluation of a low-cost IoT solution for automatic irrigation systems. The goal of this prototype was to improve the people's life quality by reducing human intervention in mechanical and/or heavy tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of ontologies in IoT applications allows better results in terms of interoperability between devices. Koprda, Š, et al [18] indicates new trends in irrigation systems and presents the design, implementation and evaluation of a low-cost IoT solution for automatic irrigation systems. The goal of this prototype was to improve the people's life quality by reducing human intervention in mechanical and/or heavy tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Irrigation automation is not exclusive to the rural sector. Studies have shown the need to improve the efficiency of urban lawn irrigation to save water, and successful strategies have been developed (Blado et al, 2017;Koprda, Magdin, Vanek, & Balogh, 2017). Asadullah and Ullah (2017) developed a low-cost and efficient design for indoor plant irrigation that reduces human labor and saves energy.…”
Section: Introductionmentioning
confidence: 99%
“…On contrary, in an agricultural environment, a different type of data and frequency of their acquiring is required (Playán et al, 2018). According to (Koprda et al, 2017) mainly weather, humidity (Jeong et al, 2018), wind direction, and strength values are needed in such conditions. Those readings are made much rarely, not creating a massive machine-to-machine communication (MMC), but devices are spread out on significantly larger distances.…”
Section: Introductionmentioning
confidence: 99%